Residents' happiness of life in rural tourism development. (June 2021) - Wang, Rong; Dai, Meiling; Ou, Yanghong; Ma, Xiaolong
Abstract: This paper explains the connotations and components of happiness and draws on a case study to explore the factors affecting residents' happiness and its effect on tourism development. A theoretical model linking community participation and residents' happiness with support for tourism development was developed. To test the model, questionnaires were administered to a sample of 376 residents in Wuyuan county, Jiangxi province, China. The results indicated three dimensions of residents' overall life happiness: material well-being, emotional well-being and self-development. Community participation was identified as a significant predictor of residents' life happiness in all three dimensions, and residents' perceptions of their overall life happiness positively affected their attitudes towards tourism development. The study differentiates happiness from the similar terms (e.g. life satisfaction, quality of life) and contributes to the better understanding and measurement of happiness by highlighting the role of self-development. Highlights: Happiness is not equal to life satisfaction or quality-of-life. Happiness consists of material wellbeing, emotional wellbeing, self-development. Community participation is a significant predictor of residents' sense of happiness. Residents' life happiness positively affects their support for tourism development.